Sustainability, Conservation and Creativity - Stewart, Pamela J. (Milton)
1 online resource (65 p.).
Keywords: By examining how small communities have dealt with forces of change and have sought to maintain themselves over time, this book offers pointers and lessons for conservation practices at all levels of society. "Sustainability" has become an increasingly popular term as a signal of concerns with long-term environmental consequences of human actions. Sustainability as a goal has started to replace "development" as a way of describing policies that go beyond the concept of increasing commercial production or making monetary profits from enterprises. By focusing on topical case histories on agricultural activity, stock-keeping, cash cropping, mining, and renewable energy, the authors highlight how ethnographic studies can and should inform policy decisions at both local and global levels. This book will be of great interest to students and scholars of applied anthropology, sociology, and development studies.